(untitled) (Sustainability in Debate, 2016)
There are severe obstacles to the realization of the environmental agenda. Both utopias of environmentalism and “simple” pragmatic challenges of environmental quality fall short. To investigate these obstacles, this analysis adopted a critical and dialectical perspective, with the support of the representation of system dynamics. The barriers faced by the environmental agenda are materially and historically structured, and operate systemically. Overcoming them depends on the simultaneous deployment of anti-systemic parameters, such as environmental information, interpretation, the training of managers and technical staff, and environmental control. Solving this problem does not require the separation of political utopias from pragmatic goals. It is possible to face the historical challenges of justice, democracy and geopolitical subordination through the environmental agenda.